The Essence of the Content of Socio-Environmental Protection in the Process of Global Environmental Problems - Rakhmatova Mukhaiyo Elboboyevna (Scientific Trends, 2025)
This article analyzes global environmental problems and their impact on the life of society. Also, the content, significance and relevance of the concept of Socio-Environmental Protection are covered on a scientific basis. The role of Socio-Environmental Protection in ensuring environmental safety, Sustainable Development and human health is considered.
Keywords: global environmental issues, social protection, environmental security, sustainable development, human and nature, environmental awareness.